Administrasi Kurikulum Pendidikan di Madrasah Aliyah Al-Fatah Palembang - Nurrohmatillah; Zahrah Chairunnisa Sukamto; Wirda Hakim (Taqrib : Journal of Islamic Studies and Education, 2026)
The implementation of the Merdeka Curriculum is a strategic effort to improve the quality of education that is adaptive to contemporary challenges and students’ needs. This study aims to analyze curriculum administration management and the implementation of the Merdeka Curriculum at Madrasah Aliyah Al-Fatah Palembang. This research employed a qualitative approach using interviews, observations, and documentation techniques. The findings indicate that the Merdeka Curriculum provides greater flexibility in planning, implementing, and evaluating learning processes. Curriculum administration planning is conducted through the development of simple and contextual teaching modules, learning implementation emphasizes project-based and contextual approaches, and evaluation is carried out holistically through formative assessments and portfolios. However, several challenges remain, particularly related to teachers’ readiness and varying levels of understanding of the Merdeka Curriculum concept. Therefore, institutional support through continuous professional development and strengthened teacher collaboration is essential to optimize the implementation of the Merdeka Curriculum.   Implementasi Kurikulum Merdeka merupakan salah satu upaya strategis dalam meningkatkan kualitas pendidikan yang adaptif terhadap perkembangan zaman dan kebutuhan peserta didik. Penelitian ini bertujuan untuk menganalisis pengelolaan administrasi kurikulum serta pelaksanaan pembelajaran Kurikulum Merdeka di Madrasah Aliyah Al-Fatah Palembang. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan Kurikulum Merdeka memberikan fleksibilitas yang lebih besar dalam perencanaan, pelaksanaan, dan evaluasi pembelajaran. Perencanaan administrasi kurikulum dilakukan melalui penyusunan modul ajar yang sederhana dan kontekstual, pelaksanaan pembelajaran menekankan pendekatan berbasis proyek dan kontekstual, serta evaluasi dilakukan secara holistik melalui penilaian formatif dan portofolio. Meskipun demikian, masih ditemukan beberapa kendala, seperti kesiapan guru dan perbedaan pemahaman terhadap konsep Kurikulum Merdeka. Oleh karena itu, diperlukan dukungan kelembagaan melalui pelatihan berkelanjutan dan penguatan kolaborasi guru untuk mengoptimalkan implementasi Kurikulum Merdeka.